Dietary changes among pregnant individuals compared to pre-pandemic: A cross-sectional analysis of the Pregnancy during the COVID-19 Pandemic (PdP) study - Vaghef-Mehrabani, Elnaz; Wang, Yanan; Zinman, Julia; Beharaj, Greis; van de Wouw, Marcel; Lebel, Catherine; Tomfohr-Madsen, Lianne; Giesbrecht, Gerald F. (Frontiers in Nutrition, 2022)
Introduction: Dietary changes are common in pregnancy and may affect pregnancy outcomes, yet these changes and the associated contributory factors during the COVID-19 pandemic have been understudied. We aimed to investigate the association between dietary change and socioeconomic variables, pre-pregnancy BMI, and mental health symptoms; the change in intake of seven food categories and their reasons; and the association between intake of these food categories and mental health symptoms. Methods: In this cross-sectional analysis, we used data from the Pregnancy during the COVID-19 Pandemic (PdP) cohort study that collected data from pregnant Canadian individuals (n=9870, gestational age ≤ 35 weeks) on socioeconomic factors, pandemic-related hardships, pre-pregnancy body mass index (BMI), dietary changes compared to pre-pandemic and the reasons for these changes. We assessed depressive and anxiety symptoms using the Edinburgh Postpartum Depression Scale (EPDS) and Patient-Reported Outcomes Measurement Information System (PROMIS)-Anxiety, respectively. Results: 54.3% of the participants reported a change in their diet. Non-white ethnicity (OR=1.33), job loss (OR=1.29), clinically elevated depressive and anxiety symptoms (OR=1.26 and 1.14, respectively), self-isolation (OR=1.20), pre-pregnancy BMI (OR=1.19), fear of COVID-19 (OR=1.15), and pandemic phase at enrolment (OR=0.90) significantly predicted dietary change. Most participants ate about the same amounts of dairy, meats and canned foods/dried goods as pre-pandemic (61.5%, 61.7%, and 60.2%, respectively), increased their intake of fresh vegetables/fruits and sweets/snacks (43.2% and 54.5%, respectively), and decreased fast-food and take-out/home delivery (53.2% and 43.1%, respectively). Changes in consumption of the food categories had a curvilinear association with mental health symptoms (except resilience) indicating greater symptoms with either decreased or increased intakes. Changes in craving, having more time for cooking/preparing foods, and being unable to go grocery shopping frequently (but not reduced affordability) were the main reasons driving these dietary changes. Conclusion: Some factors increase the odds of dietary change among pregnant individuals during the pandemic, with some changes towards a healthy and others towards an unhealthy diet. Given the importance of a healthy diet during gestation, identifying the risk and protective factors might be the first essential step in reducing the detrimental effects of unfavorable dietary changes during the pandemic on this vulnerable population.